Peningkatan Pemasaran Produk UMKM Desa Aras Kabu Menggunakan Digital Marketing - Adji Prasetia; Nurul Husna; Poppy Andriani; Sophia Salsalina4; Reflina Reflina (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
Market research is the main problem for MSMEs, but many MSMEs do not focus on understanding the market because they do not know the size and scope of the market. Since the Covid-19 pandemic has changed all forms of activities carried out by the community, the large number of people who have experienced layoffs has caused many unemployed. Generally, many home-cooked food vendors are found in small vendors. Many SMEs that have developed in this village still have traditional sales, but the existing sales are quite developed or undeveloped. And the result of this activity is that business owners will be able to operate the application well and benefit from new things that are received by the community, while increasing their knowledge of digital marketing. Keywords: Market research, Digital marketing, MSMEs, KKN Aras Kabu